Two new species of Callilepis (Asteraceae) from southern Africa with corymbose inflorescences - Herman, Paul; Koekemoer, Marinda (Phytotaxa, 2014)
Two new species of Callilepis (Asteraceae) are described: C. corymbosa and C. normae. They differ from other Callilepis species mainly by their corymbose inflorescences and white disc florets. They are endemic to the southern African region: C. corymbosa is known from Swaziland only and C. normae occurs in Mpumalanga, South Africa.